Building an Evaluation Instrument for China's Hospital Emergency Preparedness: A Systematic Review of Preparedness Instruments. (13th March 2014) - Tang, Rong; Fitzgerald, Gerard; Hou, Xiang-Yu; Wu, Yang-Ping
Abstract Objectives The aim of this report is to identify from the literature common themes relating to the concept of hospital preparedness for emergencies to develop an agreed framework for evaluation. Method A systematic literature search identified appropriate articles for critical appraisal. A meta-ethnography approach was used to synthesize the findings, using both reciprocal translation and line-of-argument synthesis. Results From an initial 2162 articles, we identified 13 articles that specifically addressed the aims of this review and formed the basis of the intended analysis. Conclusion Hospital emergency preparedness is essential for effective disaster relief. Developing a systematic and structured methodology is necessary to assess hospital preparedness. (Disaster Med Public Health Preparedness: 2014:0:1-9)